The influence of competence and work discipline on the performance of executive staff - Hidayat, Rahmat; Silviyanti, Ita Herlita; Rojul, Rojul; Lestari, Putri Indah; Haryadi, Didit (Trigin Publisher, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used associative descriptive quantitative methods with a population of 39 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that competence does not significantly influence employee performance. The second hypothesis states that work discipline significantly affects employee performance. The third hypothesis is that employee performance is influenced by competence and work discipline, which can simultaneously improve employee performance. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management.